IMPROVING STUDENTS' CRITICAL READING SKILLS THROUGH A METAPHORMING LEARNING APPROACH INTEGRATING LOCAL WISDOM AND THE FLIP APPLICATION - Lamusu, Agus Salim; Saripi, Samid (LPPM STISIPOL Mujahiddin, 2024)
This research aims to enhance students' critical reading abilities by incorporating a metaphorming method based on local wisdom and utilizing flip applications in a Reading Skills course. The study employed a classroom action research approach, conducted over two cycles. Each cycle included four phases: planning, action, observation, and reflection. Data collection methods included observations, tests, and questionnaires, which were analyzed using both qualitative and quantitative descriptive techniques. The findings revealed that integrating local wisdom-based metaphorming, specifically using Gorontalo folklore as teaching material, effectively improved students' critical reading skills. Additionally, the flip application served as an interactive learning medium, significantly boosting student engagement during the learning process. Student performance showed notable progress, with the percentage of those achieving the minimum passing grade increasing from 21.62% in the first cycle to 81.08% in the second cycle. This method demonstrated its effectiveness in enhancing both critical reading skills and students' motivation. The study recommends adopting similar approaches in other courses to foster students' critical thinking and creativity